Immunogenicity of Different Routine Poliovirus Vaccination Schedules: A Randomized, Controlled Trial in Karachi, Pakistan. (6th November 2017) - Saleem, Ali F; Mach, Ondrej; Yousafzai, Mohammad T; Khan, Asia; Weldon, William C; Steven Oberste, M; Zaidi, Syed S; Alam, Muhammad M; Quadri, Farheen; Sutter, Roland W; Zaidi, Anita K M
Abstract : Pakistan is a country where poliovirus is endemic. We assessed polio immunity achieved with different immunization schedules. The current Pakistani schedule induces high seroconversion for poliovirus types 1 and 3 but has yielded a growing cohort of children unprotected against poliovirus type 2. Abstract: Background: We assessed immunity against polioviruses induced with a new Pakistani poliovirus immunization schedule and compared it to alternative poliovirus immunization schedules. Methods: Newborns were randomized to undergo vaccination based on 1 of 5 vaccination schedules, with doses administered at birth and at 6, 10, and 14 weeks of age. Arm A received inactivated poliovirus vaccine (IPV) at all time points. Arm B received bivalent oral poliovirus vaccine (bOPV) at all time points. Arms C and D received bOPV at the first 3 time points and bOPV plus IPV at the final time point (the current schedule). Arm E received trivalent OPV (tOPV) at all time points. At 22 weeks of age, all children received 1 challenge dose of tOPV, and children in arm D received 1 additional IPV dose. Sera were analyzed for the presence of poliovirus neutralizing antibodies at birth and 14 and 22 weeks of age. Results: Seroconversion for poliovirus type 1 (PV1) at 22 weeks of age was observed in 80% of individuals in arm A, 97% in arm B, 94% in arm C, 96% in arm D, and 94% in arm E; for PV2, seroconversion frequencies were 84%, 19%, 53%, 49%, and 93%, respectively; and for PV3, seroconversion frequencies were 93%, 94%, 98%, 94%, and 85%, respectively. Conclusions: The current immunization schedule in Pakistan induced high seroconversion rates for PV1 and PV3; however, it induced PV2 seroconversion in only half of study subjects. There is a growing cohort of young children in Pakistan who are unprotected against PV2; and this creates an increasing risk of a large-scale outbreak of poliomyelitis caused by circulating vaccine-derived PV2.